2010
DOI: 10.1007/s00296-010-1567-2
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of fibromyalgia in sport professionals

Abstract: Fibromyalgia is a chronic musculoskeletal disorder characterized by widespread pain and tenderness at specific anatomic sites, commonly accompanied by fatigue [1]. The etiopathogenesis of fibromyalgia is probably multifactorial and peripheral, and central factors are thought to interact with the development of this syndrome. The true incidence and prevalence of fibromyalgia is unknown. However, studies from North America and Europe have revealed overall prevalence rates ranging from 1 to 5% in the general popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This frequency is higher than that estimated in the East Mediterranean general population which was reported to be between 0.69 % and 8.3 % with the pooled estimate of FMS prevalence being 4.43 % (18). F Inanıcı et al found a much lower frequency of FMS among sports professionals (4 out of 185 with a rate of 2.16%) (20).…”
Section: Discussionmentioning
confidence: 74%
“…This frequency is higher than that estimated in the East Mediterranean general population which was reported to be between 0.69 % and 8.3 % with the pooled estimate of FMS prevalence being 4.43 % (18). F Inanıcı et al found a much lower frequency of FMS among sports professionals (4 out of 185 with a rate of 2.16%) (20).…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, in a study, it was reported that nearly 2% of the competitive sport players had FM, which shows that people with FM may be extremely active. Although regular exercises (i.e., aerobic, strength, flexibility) are among the most important elements in the FM management, it is also important that the intensity, duration, incidence, and type of any adverse effects and frequency must be prescribed [50]. Prescribing exercises for FM patients requires extreme care.…”
Section: Exercisesmentioning
confidence: 99%